Design and Optimization of a 1x2 Rectangular Array Antenna with U-Slot for 5G Application at 26 GHz Millimeter Wave - Amillia, Fitri; Mulyono, Mulyono (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2024)
5G technology utilizes millimeter wave frequencies, particularly 26 GHz, to enable high-speed and low-latency communication services. However, the use of high frequencies presents challenges such as limited coverage area and signal penetration, requiring innovative antenna designs. This study aims to design and optimize a 1×2 rectangular array antenna with a U-slot for 5G applications operating at 26 GHz. The design process involves analytical calculations and simulations using CST Studio Suite software. The performance parameters evaluated are return loss, bandwidth, VSWR, and gain. The simulation results show that the designed antenna has a achieves a bandwidth of 3.51 GHz and a gain of 5.46 dB, which meets the desired specifications for 5G applications. In addition, the integration of U slots improves bandwidth efficiency, while the array configuration significantly improves the gain of the antenna. This antenna is expected to provide effective support for 5G network, along with the increasing demand for robust and efficient wireless communication systems.  Keywords: Antenna array, microstrip, U-slot, millimeter wave, 5G